(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research on the impact of e-banking service quality on customer satisfaction in Tirunelveli district provides a comprehensive analysis of how various service dimensions contribute to customer experience and loyalty. Key service quality dimensions, such as reliability, responsiveness, ease of access, security, and personalization, were examined to assess their influence on customer satisfaction. The study also emphasizes the growing importance of mobile banking and internet banking, with a focus on how user-friendly interfaces, transaction speed, and seamless navigation can enhance customer engagement. Additionally, the research considers the role of demographic factors such as age, education, income levels, and digital literacy in moderating the relationship between service quality and customer satisfaction. The results highlight that customers in Tirunelveli are particularly concerned with the security and privacy of their online transactions, along with prompt customer support in case of issues. Banks that offer superior e-banking services are more likely to retain customers, increase satisfaction, and build long-term trust. The study concludes that continuous innovation and improvement in e-banking services are crucial for enhancing customer satisfaction, especially in regions like Tirunelveli, where digital banking is rapidly growing. For this study both primary data and secondary data has been collected. Convenience sampling method was used to gather 110 respondents has been used from Tirunelveli district in order to obtain the relevant data.